2022
DOI: 10.1186/s12883-022-02737-8
|View full text |Cite|
|
Sign up to set email alerts
|

Early neurological deterioration in acute ischemic stroke patients after intravenous thrombolysis with alteplase predicts poor 3-month functional prognosis - data from the Thrombolysis Implementation and Monitor of Acute Ischemic Stroke in China (TIMS-China)

Abstract: Background We aimed to investigate the risk factors of early neurological deterioration (END) after intravenous thrombolysis with recombinant tissue-type plasminogen activator (rt-PA) and the relationship between END and poor 3-month functional outcomes. Methods Patients who accepted intravenous recombinant rt-PA were enrolled continuously. END was defined as an increase in National Institute of Health Stroke (NIHSS) score ≥ 4 points or death withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 28 publications
3
9
0
Order By: Relevance
“…In our study, patients with END, history of diabetes and NIHSS score at discharge are associated with poor functional outcome at 3-month follow-up. Patients suffered from END during the stroke course would have 8.22-fold increased risk of poor functional outcome, which is consistent with previous studies [ 4 , 25 , 42 – 44 ]. Diabetes is confirmed as an independent risk factor for ischemic stroke and may be associated with poor outcomes in previous studies [ 45 , 46 ].…”
Section: Discussionsupporting
confidence: 91%
“…In our study, patients with END, history of diabetes and NIHSS score at discharge are associated with poor functional outcome at 3-month follow-up. Patients suffered from END during the stroke course would have 8.22-fold increased risk of poor functional outcome, which is consistent with previous studies [ 4 , 25 , 42 – 44 ]. Diabetes is confirmed as an independent risk factor for ischemic stroke and may be associated with poor outcomes in previous studies [ 45 , 46 ].…”
Section: Discussionsupporting
confidence: 91%
“…This study revealed that VEND had a significant detrimental impact on 3-month functional outcomes, in concordance with previous findings for END. 29,30 Of note, this study further revealed that VEND significantly predicted poor outcomes in both minor and non-minor stroke patients. A prior study showed that 12% of patients who received thrombolysis therapy for acute minor ischemic stroke due to large vessel occlusion developed ischemic END and 48% of the END occurred within 2 h, which was associated with worse 3-month functional outcomes even after rescue thrombectomy.…”
Section: Discussionsupporting
confidence: 59%
“…They suggested that the accuracy of the nomogram needs to be improved. A recent study led by Wang yongjun group identified serum glucose level is an independent risk factor in the poor 3-month functional recovery in stroke patients with the univariate and multivariate logistic regression study ( Che et al, 2022 ). Mehta et al also used the logistic regression study to find DM, dyslipidemia, baseline NIHSS, random blood sugar, dense cerebral artery sign, age and glucose level on admission were predicting factors in poor outcome ( Mehta et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%